Development of titanium-based scaffolds for spinal prosthesis - Wang, Jun Kit. (2012)
The author was selected to join Assistant Professor Cleo Choong research group together with a collaboration project with Singapore Institute of Manufacturing Technology, Singapore for his Final Year Project with the project title as “Development of Titanium-based Scaffolds for Spinal Prosthesis”. Throughout this project, the author was under the guidance of Assistant Professor Cleo Choong as School of Materials Science & Engineering supervisor, Nanyang Technological University as well as Dr. He Zeming and Dr. Saeed Maleksaeedi as direct institute supervisors.